The death of Korean fir (Abies koreana) affects soil symbiotic fungal microbiome: Preliminary findings - Jeong, Minsoo; Tagele, Setu Bazie; Kim, Min-Ji; Ko, Suk-Hyung; Kim, Kwon-Su; Koh, Jung-Goon; Jung, Da-Ryung; Jo, YoungJae; Jung, YeonGyun; Park, Yeong-Jun; Kim, Min-Sueng; Lim, Kyeongmo; et al. (Frontiers in Forests and Global Change, 2023)
The population of the Korean fir, Abies koreana, is declining at an accelerating rate, and the average mortality rate in 2019 exceeded 36.43% on Mt. Hallasan in Jeju Island, Republic of Korea. Several prior studies have reported different reasons with various interpretations, indicating that additional data, such as data on microbial communities that promote plant growth and resistance to abiotic stresses, are required to understand the phenomenon further. This is the first investigation that documents the changes in the soil microbial and fungal community and soil physicochemical properties resulting from the death of the Korean fir. In our case, high throughput sequencing data have been provided for the soil microbiome and mycobiome of Korean fir trees, identifying the microbial composition differences before and after the decline in the health of Korean fir trees. The results showed that the soil fungal community was considerably shaped in response to the decline in the health of Korean fir rather than the soil bacterial community. The decline in health or the death of Korean fir trees contributed to the decrease in diversity and dominance of symbiotic fungi such as Russula, Sebacina, and Phenoliferia in the forest ecosystem. It also weakened the complexity and ecological competition of the fungal co-occurrence network. Structural equation modeling showed that the death of Korean fir was strongly associated with the concentrations of soil nutrients such as available phosphorus (P2O5) and potassium ion (K+) concentrations and low moisture content, adversely affecting the symbiotic relationship with ectomycorrhizal fungi. Our findings shed light on the critical taxa of mycobiome of live and dead A. koreana plants and their relationship with ecological edaphic factors, highlighting their potential role as biomarkers for the death of Korean fir.